1997
DOI: 10.1099/00221287-143-10-3149
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coli is unable to produce pyrroloquinoline quinone (PQQ)

Abstract: Many bacteria can synthesize the cofactor pyrroloquinoline quinone (PQQ), a cofactor of several dehydrogenases, including glucose dehydrogenase (GCD). Among the enteric bacteria, Klebsiella pneumoniae has been shown to contain the genes required for PQQ biosynthesis. Escherichia coli and Salmonella typhimurium were thought to be unable to synthesize PQQ but it has been reported that strain EF260, a derivative of E. coli FB8, can synthesize PQQ after mutation and can oxidize glucose to gluconate via the GCD/PQQ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
71
0
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(73 citation statements)
references
References 39 publications
1
71
0
1
Order By: Relevance
“…Notably, the E. coli wild-type quinol fumarate reductase, which bears a single exchangeable Q-site where either UQ or MQ can bind, is unable to stabilize semiquinone radicals of both UQ and MQ, but rather a mutation is required for the stabilization (9). Under general growth conditions in which no PQQ is supplied because of an inherent lack of PQQ-synthesizing genes in E. coli (30), bound Q may accept electrons from reduced bulk Q, which might contribute to scavenging extra electrons in the membrane.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, the E. coli wild-type quinol fumarate reductase, which bears a single exchangeable Q-site where either UQ or MQ can bind, is unable to stabilize semiquinone radicals of both UQ and MQ, but rather a mutation is required for the stabilization (9). Under general growth conditions in which no PQQ is supplied because of an inherent lack of PQQ-synthesizing genes in E. coli (30), bound Q may accept electrons from reduced bulk Q, which might contribute to scavenging extra electrons in the membrane.…”
Section: Discussionmentioning
confidence: 99%
“…coli mGDH has been shown to be expressed under both aerobic and anaerobic conditions, although the expression level under the latter condition is relatively low (29). mGDH is a good model for primary dehydrogenases in terms of its occurrence as a single protein and as an apo-protein (30), which allows study with both forms of apo-and holo-enzymes (31). This model might provide valuable information on the physiological function of bound Q.…”
mentioning
confidence: 99%
“…Membrane-bound glucose dehydrogenase (mGDH) is a good model for primary dehydrogenases in terms of its occurrence as a single protein and as an apo-protein (Yamada et al, 1993a;Matsushita et al, 1997;Elias & Yamada, 2003), which allows study with both forms of apo-and holo-enzymes (Ameyama et al, 1985). It has been demonstrated that mGDH has two quinone (Q)-binding sites, one (Q I ) for bound Q and the other (Q II ) for bulk Q (Elias et al, 2004), which is near the membrane surface rather than in the hydrophobic interior (Miyoshi et al, 1999), and that intramolecular electron transfer following the catalytic reaction occurs from PQQH 2 directly to Q in the Q II site or via bound Q (Fig.…”
Section: Menaquinone As Well As Uq As a Bound Quinone Is Crucial For mentioning
confidence: 99%
“…GDH is an 88-kDa monomeric protein with five transmembrane segments at the N-terminal portion (residues 1-140), which ensure a strong anchorage of the protein to the inner membrane (4,5). The remaining large C-terminal portion (residues 141-796) has a catalytic domain including PQQ-(6, 7) and Ca 2ϩ or Mg 2ϩ -binding sites (8,9) that is located in the periplasmic side. A model structure of GDH based on the x-ray crystallographic structure of the ␣-subunit of MDH in Methylobacterium extorquens has been proposed (10), and the putative structure of the PQQ-binding catalytic site has been further confirmed and characterized by mutagenic analysis of several amino acid residues around PQQ (11)(12)(13)(14)(15).…”
mentioning
confidence: 99%
“…Bacterial Strains, Plasmids, and Media-The E. coli K-12 strains used in this study were PPA322 (⌬(ptsH ptsI crr) galP::Tn10), derived from the wild-type FB8 strain (9), and YU423 (PPA322 gcd::cm) (9). The plasmids used were pMC1396 (ЈlacZ lacYA amp r ) (24), pTTQ18 (lacZ␣ lacI q amp r ) (25), and pUCGCD1 (amp r gcd) (26).…”
mentioning
confidence: 99%